Empty House - Pilcher, Rosamunde (Thorndike Press Thorndike, Maine, 1992)
Do you believe in second chances? Virginia does. That$1 (Bs why she takes her two children back to Cornwall and rents a house near the man she loved when she was seventeen. And this time, she$1 (Bs determined to make the right decision.s
68577
Keywords: Large Type Books; Love Story